(untitled) (Interdisciplinary Research in Education, 2022)
The study Entitled “Observational studies on personal hygiene and sanitation practices of elderly Buddhists" was conducted in Kathmandu Valley. The main objective of this study was to analyze the personal hygiene and sanitation practices of elderly Buddhists. The study was based on descriptive design with qualitative and quantitative nature. Convenient sampling method was applied to collect the data and altogether 640 elderly Buddhists including of 320 male and 320 female were selected as a sample for study. Similarly, observation checklist with direct observation method was used for data collection. The three dimensions for hygiene and sanitation condition measurement such as satisfactory, good and poor were used. Out of total respondent, the most of the respondents (40.16%) were in age Group 60-64 years. The highest sex ratio (141.17) was found in 75-79 years age group and the lowest sex ratio (80.00) was found in 80 years and above age group. The mean age of male elders was 68 years and 67.36 years for female. Around 48% of elderly Buddhist had moderate condition of personal hygiene practices, nearly 40% respondents had satisfactory and around 12% elders had poor hygiene practices. Similarly, 39% elders had satisfactory sanitation practices, 42% respondents had moderate and 19% respondents had poor sanitation practices. As conclusion, most of the elders were practicing with moderate hygiene practices. The moderate condition negatively affects the health condition of Buddhists elders. Most of the elders were practicing with satisfactory sanitation practices the also affects the wellbeing of the Buddhists elders in Kathmandu Valley.